PENGEMBANGAN KOMPETENSI GURU BAHASA ARAB MELALUI IMLA SEBAGAI ORGANISASI PROFESI - Muradi, Ahmad (Arabi : Journal of Arabic Studies, 2016)
This study aims to explain the role of IMLA in developing Arabic teacher competences. Indeed a teacher is a precious profession, carrying valuable tasks to educate and build character of the nation. Teacher is a precious profession to create a good life. Therefore, teacher should develop their competences including Arabic language teacher. The intended competences in Arabic language learning are language competence, communicative competence, and cultural competence. IMLA is the abbreviation of (Ittihad Mudarrisi al-Lughah al-‘Arabiyyah), a organization established to build and develop Arabic teachers’ competences in Indonesia. This opportunity is given to Arabic teachers in IMLA organization to affiliate with its agendas, management, and association in local, national, and international scope. There are many information will be gained through the various agendas to develop teachers’ competence. For the example is like attending seminars, workshops, and other trainings held by the organization. IMLA organization is able to connect local teachers and lecturers to the foreign ones especially from Arabic emirate countries.DOI: 10.24865/ajas.v1i2.2